Chapter Introduzione - FILI', Valeria (Proceedings e report, 2023)
In introducing the first session, the A. stresses that gender issues are now central to our country's cultural, political, and social-economic agenda, and how the promotion of inclusive language is important for the social and legal recognition of categories of discriminated or otherwise marginalized. by an autograph manuscript by Lope and another one transmitted through printed books and sueltas. On the other hand, I will focus my attention on the dialogues in the play, since they are useful to better understand the work of composition and preparation of the copy of the comedia by the playwright, as well as the company's work on the text.